Antecedent Factors and Locus of Control: Their Impact on Financial Management Behavior MSME Actors - Sumarni Sumarni; Maswanto (Jurnal Bisnis dan Manajemen, 2026)
This study examines the configuration of financial behavioral attributes Financial Attitude, Financial Knowledge, and Locus of Control that shape the financial management behavior of Micro, Small, and Medium Enterprise (MSME) actors. While these factors are often studied in isolation, a significant gap exists in understanding how they combine to form a holistic psychological profile for financial decision-making. The purpose of this research is to deconstruct and quantify the influence of these three attributes, particularly by evaluating the mediating role of Locus of Control. Employing a quantitative approach, survey data were collected from 97 MSME actors. Multiple regression analysis tested the direct effects, and path analysis was used to assess mediation. The results revealed that both Financial Knowledge and Financial Attitude have a significant positive effect on financial management behavior, with knowledge exhibiting a slightly stronger influence. Locus of Control partially mediates both relationships, acting as a key psychological mechanism through which cognitive and affective factors translate into behavior. The direct effect model explained 42.1% of the variance in financial management behavior. A key limitation is the cross-sectional design and reliance on self-reported data from a specific sample, which limits causal inference and generalizability. Future research should employ longitudinal designs and incorporate objective financial performance measures to better capture actual behavioral outcomes.